User’s Hand Effect on Efficiency of 2-port 5 GHz Mobile Terminal Antennas - Muhammad Nor Che Isa, Che; Abdullah Al-Hadi, Azremi; Norlyana Azemi, Saidatul; Khan, Rizwan (Bulletin of Electrical Engineering and Informatics, 2019)
In this paper, the influence of user’s hand on mobile terminal antenna when it placed approximately on top of Multiple Input Multiple Output radiating element antennas (PIFAs) is studied extensively. The antenna is designed to operate at 5 GHz with 1.5 GHz of -6 dB bandwidth. The effect of user’s hand with different finger positions are studied at seven positions on slit at the ground plane, seven differences height above the antenna and nine different locations around the radiating element at 2 mm height from antenna. The losses due to presence of hand are studied in terms of scattering parameters, radiation efficiency and matching efficiency. The maximum loss in term of isolation in the presence of user’s hand is found at 6 mm on the slit and it decreased as the hand move away from the slitted area on the ground plane. The maximum efficiency loss is observed when the finger is placed right on top of the radiating element with -5.85 dB compare to antenna without the presence of user’s hand. On the other hand, the result for matching efficiency indicates approximately 0.2 dB losses occurred when the fingers are varied at different height and position.